"Don't Get Weak in Your Compassion": Bereaved Next of Kin's Suggestions for Improving End‐of‐Life Care in Veterans Affairs Medical Centers. Issue 4 (21st March 2014) - Riggs, Jennifer S.; Woodby, Lesa L.; Burgio, Kathryn L.; Amos Bailey, F.; Williams, Beverly R.
<x xml:space="preserve">Abstract</x> Objectives To analyze bereaved next of kin's suggestions for improving end‐of‐life (EOL) care in Veterans Affairs (VA) Medical Centers (VAMCs). Design Qualitative. Setting This study was part of a larger study testing the effectiveness of a multimodal intervention strategy to improve processes of EOL care in six southeast U.S. VAMCs (Best Practices for End‐of‐Life Care for Our Nation's Veterans—BEACON Trial). Participants Bereaved next of kin (n = 78) of veterans who died between 2005 and 2010. Measurements Data addressing praise, criticism, and recommendations for enhancing EOL care were abstracted from semistructured interviews of next of kin and aggregated into a code labeled "Suggestions." Content analysis proceeded iteratively through data review, comparison, and negotiation of emergent themes and integration of all coauthors' insights and interpretations into the evolving interpretive scheme. Results Next of kin provided examples that resonated with their conceptions of quality EOL care. They also described distressing situations and perceptions of deficits in care. Major themes derived were compassionate care, good communication, support for family visits and privacy, and the need for death preparation and postdeath guidance. The fifth theme, unique to this study, was the salience of the relationship between the veterans and their families and the VA and the expectations this engendered in terms of dignity and honor. Conclusion Interventions that support staff's ability to convey compassion, communicate information to families and other staff, listen to patients and families, prepare families for the individual's death, and provide consistent, coordinated information regarding after‐death activities may optimize EOL hospital care for veterans.